Diversity Intelligence as a Source of Strength in Human Resource Development: Increasing the Presence of Women Pilots. Issue 3 (August 2018) - Opengart, Rose; Germain, Marie-Line
The Problem: Although more women have been entering the workforce in the past few decades, this progress has not readily been seen in the field of aviation. Indeed, of all current U.S. corporate and commercial pilots, women only account for 6%. Through a diversity intelligence (DQ) perspective, the authors explore the experiences of women pilots to identify ways of increasing female representation in male-dominated fields in general and in aviation in particular. Via a phenomenological qualitative research approach, a total of 33 female pilots were surveyed and an additional 20 participated in a one-on-one interview. NVivo qualitative data analysis software was used, employing an inductive constant comparative method to develop categories. The Solution: Results indicate that female pilots face significant gender-related roadblocks to their careers. Human Resource Development (HRD) practitioners can help organizations increase DQ to recruit and retain women in nontraditional occupations and industries. Increasing DQ would create a more welcoming environment for both women and minorities. It would also address cultural and organizational issues such as tacit and subtle discrimination, increase the presence of role models, provide support systems, and assist with cultural change to eliminate the good old boy mentality. The Stakeholders: Industry leaders, women, and HRD professionals.